2021
DOI: 10.1002/1348-9585.12214
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and site-specific incident risks of musculoskeletal disorders among 224 506 workers in the food and beverage service industry in Taiwan: A 15-year Nationwide Population-Based Cohort Study

Abstract: Objectives Occupational characteristics in the food and beverage service industry (FBSI) have been found to be associated with musculoskeletal disorders (MSDs). This study aimed to examine gender and site‐specific incident risks of MSDs among FBSI workers in Taiwan using a national population‐based database. Methods We conducted a 15‐year population‐based cohort study among 224 506 FBSI workers in Taiwan using data from five large nationwide databases to estimate direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(32 reference statements)
1
11
0
2
Order By: Relevance
“…Our study revealed ( Figure 1 ) a gender difference in work-related MSDs in sector I. Similar to other studies [ 7 , 8 ], MSDs occur more frequently in female workers in almost all body regions. The observed gender difference was particularly pronounced in older workers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study revealed ( Figure 1 ) a gender difference in work-related MSDs in sector I. Similar to other studies [ 7 , 8 ], MSDs occur more frequently in female workers in almost all body regions. The observed gender difference was particularly pronounced in older workers.…”
Section: Discussionsupporting
confidence: 90%
“…Sector I “accommodation and food service activities” of the classification NACE Rev2 seems to require additional attention and specific countermeasures to reduce MSDs [ 7 , 10 , 11 ]. This industry contributes significantly to employment and the economy in the EU [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Faktor Alter spielte in der vorliegenden Studie als Einflussparameter keine Rolle, da es keine signifikanten Unterschiede im Alter in den Berufszweigen gab. Dies zeigte sich in vorangegangenen internationalen Studien divergent [25][26][27].…”
Section: I L I T ä Runclassified
“…So sind Erwerbstätige bestimmter Berufssektoren einem höheren Verletzungsrisiko am Arbeitsplatz ausgesetzt als andere [33]. Der Beruf spielt aber auch insofern eine Rolle, als dass die Tätigkeitsausübung bei ein und derselben gesundheitlichen Einschränkung berufsabhängig unterschiedlich stark beeinträchtigen und somit spezifische sekundäre gesundheitsbezogene Risiken nach sich ziehen kann [26]. So zeigen sich bei Personen mit einer RM-Läsion, die in einem Berufssektor mit wenig Belastung der oberen Extremität tätig sind, eine geringere Gesamtdauer der Arbeitsunfähigkeit im Vergleich zu Personen, deren berufliche Ausübung mit langen oder starken Belastungen der oberen Extremität verbunden ist.…”
Section: I L I T ä Runclassified